1999
DOI: 10.1074/jbc.274.21.14609
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Carboxylate Ligation at the Active Site of Photosystem II

Abstract: Photosystem II (PSII) is the photosynthetic enzyme catalyzing the oxidation of water and reduction of plastoquinone (Q). This reaction occurs at a catalytic site containing four manganese atoms and cycling among five oxidation states, the S n states, where n refers to the number of oxidizing equivalents stored. Biochemical and spectroscopic techniques have been used previously to conclude that aspartate 170 in the D1 subunit influences the structure and function of the PSII active site (Boerner, R. J., Nguyen,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 42 publications
3
28
2
Order By: Relevance
“…2A, solid line). In agreement with our published work (35), alteration in illumination time from 10 min to 1 min had no effect on the spectrum obtained. The inset in Fig.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…2A, solid line). In agreement with our published work (35), alteration in illumination time from 10 min to 1 min had no effect on the spectrum obtained. The inset in Fig.…”
Section: Resultssupporting
confidence: 82%
“…Illumination at this temperature has been used to acquire the S 2 Q A Ϫ -minus-S 1 Q A vibrational spectrum (21,31,32,35). The spectroscopic results that we have presented here are consistent with a deprotonation reaction, accompanying the S 1 to S 2 transition.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…1, A-C, represent S 2 Q A Ϫ -minus-S 1 Q A difference spectra acquired from PSII samples containing natural abundance, [ 13 C]Glu/Gln-, or [ 13 C]Asp/Asn-labeled MSP, respectively. The 12 C MSP spectrum is similar to data obtained previously at this temperature (25,29,47,51). Because all the spectra were corrected for path length and concentration, they were directly subtracted on a one to one basis, to generate the isotope-edited spectrum (Figs.…”
Section: Resultsmentioning
confidence: 74%
“…The origin of these spectral differences has been discussed previously (35,36). Assignments of the 200 K spectra, based on global isotopic labeling and site-directed mutagenesis, have been described (25,29,47,51). In particular, at 200 K, our previous isotope editing work has shown that a subset of the carboxylates, contributing to the spectra, is on MSP (23).…”
Section: Discussionmentioning
confidence: 99%